2020
DOI: 10.1371/journal.pone.0227725
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of ESBL-producing Enterobacteriaceae from the gut of healthy chickens, Gallus gallus domesticus in rural Nepal: Dominance of CTX-M-15-non-ST131 Escherichia coli clones

Abstract: The surge in the prevalence of drug-resistant bacteria in poultry is a global concern as it may pose an extended threat to humans and animal health. The present study aimed to investigate the colonization proportion of extended-spectrum β-lactamase (ESBL) and carbapenemase-producing Enterobacteriaceae (EPE and CPE, respectively) in the gut of healthy poultry, Gallus gallus domesticus in Kaski district of Western Nepal. Total, 113 pooled rectal swab specimens from 66 private household farms and 47 commercial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…e study reports an overall prevalence of ESBL-/AmpC-EC of 17.5%, which was lower when compared to a range of 20% to 87% compiled from other studies [11][12][13]23]. e variations in prevalence rates could be the difference in ESBL/AmpC diagnostic methods used.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…e study reports an overall prevalence of ESBL-/AmpC-EC of 17.5%, which was lower when compared to a range of 20% to 87% compiled from other studies [11][12][13]23]. e variations in prevalence rates could be the difference in ESBL/AmpC diagnostic methods used.…”
Section: Discussionmentioning
confidence: 82%
“…Poultry management systems in Uganda were categorized into intensive, semi-intensive, and extensive. In this study, we concentrated on intensive farms since they are more popular [ 17 ] and a high consumer of antibiotics which increases the risk of birds carrying resistant bacteria [ 12 ]. The inclusion criteria excluded farms with less than 100 birds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, antibacterial abuse was already found as a significant factor in the selection and development of antibiotic-resistant microorganisms in clinical treatment (11). In the experiment was performed (12), the findings of antibiotic resistance screening towards 15 antimicrobial drugs revealed that all 78 (one hundred percent) E. coli isolates tested positive for penicillin resistance (penicillin, ampicillin, and amoxicillin).…”
Section: Susceptibility Testingmentioning
confidence: 99%
“…Previous studies reported the presence of ESBLproducing E. coli and CREC in food-producing animals (Köck et al, 2018;Hosuru Subramanya et al, 2020). However, little is known regarding the spread of ESBLproducing E. coli and CRE among livestock animals in Malaysia.…”
Section: Introductionmentioning
confidence: 99%